Digital School Implementation at SMA Negeri 1 City of Sukabumi - Mulyana, Rachmat; Hadian, Tantan; Tejawiani, Ida; Ikhwan Awaluddin, Asep (Journal of World Science, 2023)
Digital schools are essential for new experiences in the classroom and the education system as a whole for teachers and students, with the flood of new technologies, of course, demanding changes to the way teachers teach and learn students. This research aims to describe and analyze the implementation of digital school at SMAN 1 Sukabumi. This research uses a qualitative approach with a descriptive method. The respondents of this study were the principal, four deputy principals, teachers and 293 students. Data collection was carried out using documentation studies, observations, and interviews. The data obtained, collected, processed, and conclusions are drawn. The results of this study are that in school planning, this program has been planned to start in 2013 but has yet to have a grand design digital school program, both short-term and long-term. The organization of the program still needs to be directed. Meanwhile, in its implementation, SMA Negeri 1 Sukabumi has gradually implemented the digitization program. However, it still needs to be completed and comprehensive. The principal has carried out an internal evaluation. However, it still needs to evaluate the digital school program. Meanwhile, external supervision has yet to be carried out either by school committees or school supervisors. The school has planned a digital school program, with the formulation of the school's vision, mission and goals that lead to the development of a digital-based school. However, there must be a clear grand design for both short-term and long-term programs.